Protective Effect of Helix aspersa Extract against Spleen and Liver Injuries Induced by N-Nitroso Methyl Urea in Mice - Ibtissem EL OUAR, Hajer ATOUI, Ihcène DRAA, Cherifa AGGOUNE, Dalila NAIMI & (Journal of Applied Pharmaceutical Science, 2015)
Objective: This study was carried out to investigate the protective effect of an aqueous extract, from the garden snail Helix aspersa (Mollusca, pulmonate), against N-nitrosomethylurea (NMU) induced damage in mice. Methods: Haematoxylin/ Eosin based histology was performed to evaluate the morphological changes in liver and spleen. Results: our results show that NMU causes different damages in liver and spleen. It induces alterations of blood system of the two organs with the apparition of hemangioma. The histological assessment shows that H. aspersa extract markedly reduces the damage induced by the carcinogen and preserved the histo-architecture of these tissues. Furthermore, histopathological finding demonstrates that H. aspersa extract increase immune system activity through the stimulation of immune cell penetration in liver and differentiation of macrophages into foreign body giant cells.Conclusion: These results suggest that H. aspersa extract acts as a potent hepatic and spleen protective agent against NMU carcinogenesis.
Keywords: N-nitrosomethylurea, carcinogenesis. Helix aspersa, aqueous extract.